How Advanced are Conductive Nanocomposite Hydrogels for Repairing and Monitoring Myocardial Infarction? - Liu Y; Liu D; Xue Y; Sun H; Zhan X; Sun L; Kang K (International Journal of Nanomedicine, 2025)
Yang Liu,1,* Donghui Liu,1,* Yanghong Xue,1,* Haobo Sun,1 Xu Zhan,1 Lihua Sun,2 Kai Kang1,3,4 1Department of Cardiovascular Surgery, The First Hospital of Harbin Medical University, Harbin, 150000, People’s Republic of China; 2Department of Cardiovascular Surgery, The First Affiliated Hospital of Harbin Medical University, and Department of Pharmacology, College of Pharmacy, Harbin Medical University, Harbin, 150081, People’s Republic of China; 3Key Laboratory of NHC Cell Transplantation, The First Hospital of Harbin Medical University, Harbin, 150000, People’s Republic of China; 4Key Laboratory of Liver and Spleen Surgery, Ministry of Education, The First Affiliated Hospital of Harbin Medical University, Harbin, 150000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kai Kang, Department of Cardiovascular Surgery, The First Affiliated Hospital of Harbin Medical University, Harbin, 150000, People’s Republic of China, Email kangkai1975@sina.com Lihua Sun, Department of Cardiovascular Surgery, The First Affiliated Hospital of Harbin Medical University, and Department of Pharmacology, School of Pharmacy, Harbin Medical University, Harbin, 150081, People’s Republic of China, Email sunlihua0219@163.comAbstract: Myocardial infarction (MI) remains the leading cause of death worldwide. Cardiomyocytes, being terminally differentiated cells, have limited regenerative capacity. Following an MI, myocyte necrosis and ventricular dilation can lead to heart failure. While current treatments for heart disease—such as pharmaceuticals, coronary interventions, coronary artery bypass grafting, cellular therapy, and heart transplantation—offer some relief, their effectiveness is limited, particularly in patients with severe myocardial damage. Recent advancements in cardiac tissue engineering have introduced a range of materials aimed at repairing the heart, with conductive hydrogels emerging as a promising approach. These materials, which include metallic nanomaterials, conductive polymers, carbon-based conductive materials, and other specialized types of conductive substances, exhibit excellent electrical conductivity, tunable mechanical properties, and biomimetic features. As a result, they are increasingly being considered for myocardial repair. This review explores the application of conductive hydrogels in treating myocardial infarction, highlighting recent research in various types of conductive hydrogels. These are categorized by their nanomaterial composition, including hydrogels designed for cell culture scaffolds, patch-type hydrogels, and injectable conductive hydrogels. Additionally, electrophysiological monitoring during MI is gaining importance in understanding disease progression and prognosis. In recent years, conductive hydrogels have rapidly evolved to serve as tools for real-time monitoring of signal changes, while their electroresponsive properties open new possibilities for targeted drug delivery in infarct therapy.Keywords: myocardial infarction, conductivity, nanomaterials, hydrogel, cardiac tissue engineering